Revisiting the classics on secularization theory - Gülalp, Haldun (Frontiers in Sociology, 2025)
Secularization theory's sway has waned since the end of the 20th century, but the myth that the “founding fathers” of sociology were pioneers of this theory has survived. This article aims to demolish this myth through a comparative analysis of the works of Karl Marx, Max Weber, and Emile Durkheim, and raises fresh questions about the concept of secularization.